Strategi Guru Pendidikan Agama Islam dalam Membentuk Karakter Religius Peserta Didik Sekolah Dasar - Tiara Ayu Astriana; Ikhwan Aziz Q; Rina Mida Hayati (Bustanul Ulum Journal of Islamic Education, 2023)
In Islamic religious education and ethics (often called PAI and BP) learning materials at SDN 2 Kesumadadi, there is material that discusses having faith in Allah through Asmaul Husna. In this material, the PAI teacher introduces the complete Asmaul Husna by carrying out the habituation of reading Asmaul Husna. Even though this material only discusses the 4 Asmaul Husna. The habituation of reading Asmaul Husna is a form of the effort carried out by PAI teachers to shape the religious character of the students at SDN 2 Kesumadadi, so that religious values are instilled in the souls of students. This research is qualitative research with the type of field research. Data collection techniques were carried out through observation, interviews, and documentation. The results of this study indicate that the habit of reading asmaul husna is not done every day, but only every religious lesson. The efforts of PAI teachers in forming religious character through the habit of reading asmaul husna in SDN 2 Kesumadadi are carried out in several ways, including through exemplary, habituation, mentoring, appreciation, and discipline.